Jawabanmu

2014-06-05T19:47:21+07:00
 \lim_{x \to \2}2   \frac{x^{2}+x-6 }{x^{2}-5x+6 }
= \lim_{x \to \2}2  \frac{(x+3)(x-2) }{(x-3)(x-2) }
= \lim_{x \to \2}2  \frac{x+3}{x-2}
= \frac{2+3}{2-3}
=5/(-1)
=-5

\lim_{x \to \3}3  \frac{9-x^{2} }{4- \sqrt{x^{2}+7} }
= \lim_{x \to \3}3  \frac{9-x^{2} }{4- \sqrt{x^{2}+7} }  \frac{{4+\sqrt{x^{2}+7} } }{4+\sqrt{x^{2}+7} }
=\lim_{x \to \3} 3 \frac{(9- x^{2} )(4+ \sqrt{ x^{2} +7} )}{16-( x^{2} +7)}
=\lim_{x \to \3} 3 \frac{(9- x^{2} )(4+ \sqrt{ x^{2} +7} )}{9-( x^{2} )}
= \lim_{x \to \3}3 (4+ \sqrt{ x^{2} +7)}
=4+√(3²+7)
=8